Leadership and its role in intellectual migration and creativity development - Oliinyk, Olena; Mishchuk, Halyna; Bilan, Yuriy (Creativity Studies, 2024)
The study aims to investigate the role of leadership in creativity development, including opportunities arising from the attractiveness of countries for intellectual migrants. Using the authors’ approach for assessing leadership development in the European Union, it is found that the leading positions belong to Finland with an integral index value of 0.85, Denmark (0.83), and the Netherlands (0.76). To test hypotheses about the significant influence of leadership on the attractiveness of countries for intellectual migrants and creativity development, correlation analysis was used. Creativity development was analysed based on the most frequently used indicators of creative economics dynamics. Besides, it was considered that the most obvious result of creative thinking is the innovation development of the countries. The resulting pairwise correlation coefficients for the European Union show a strong relationship between the level of leadership and a country’s ability to attract (0.73) and retain talent (0.80). A positive impact of leadership on creativity development is confirmed by the links with the overall value of the Global Innovation Index (0.79), the growth of innovative companies (0.81), creative outputs (0.58), and cultural employment (0.68). The obtained results prove the need for the development of leadership competencies as an important driver of creativity, talent attraction and generation of innovative solutions.